A prospective study to assess clinicopathological correlation of head and neck masses - Sahni, Dimple; Kaur, Amandeep; Bansal, Archu; Chawla, Sagar; Bedi, Neeru; Sahni, Priya (International Journal Of Community Medicine And Public Health, 2024)
Background: One of the most frequent clinical manifestations in the field of otorhinolaryngology is a mass in the head and neck area. A thorough history and good clinical examination including the findings of inspection and palpation are key factors for near accurate provisional diagnosis but histopathological is the gold standard for confirmation. FNAC is an easy, efficient, and affordable way to sample superficial neck masses. Methods: The present research has been performed on 100 patients presenting with clinically palpable head and neck masses in the ENT OPD of Rajindra Hospital, Patiala for duration of 2 years (2021-2023). Clinical diagnosis was correlated with cytology and histopathology findings. The data was compiled and evaluated using adequate statistical tools. Results: In this research, 100 cases of head and neck swellings were examined. Out of 100 swellings, 39 patients had lymph node swellings, 31 presented with thyroid swelling, 20 had salivary gland swelling and 10 were miscellaneous. In this study, most of the swellings found to be inflammatory in nature. Women were far more likely to be involved than men. Clinical and cytological diagnoses were made in all cases. Conclusions: When compared to a biopsy, the procedure of fine needle aspiration cytology for head and neck swellings is not only less invasive but also more cost-effective, and causes far less pain. It is possible to execute the procedure successfully on elderly people and children without the need for anesthesia.